2013
DOI: 10.1186/1556-276x-8-375
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser modification of an array of vertically aligned carbon nanotubes intercalated with Fe phase nanoparticles

Abstract: Femtosecond lasers (FSL) are playing an increasingly important role in materials research, characterization, and modification. Due to an extremely short pulse width, interactions of FSL irradiation with solid surfaces attract special interest, and a number of unusual phenomena resulted in the formation of new materials are expected. Here, we report on a new nanostructure observed after the interaction of FSL irradiation with arrays of vertically aligned carbon nanotubes (CNTs) intercalated with iron phase cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(52 reference statements)
1
7
0
1
Order By: Relevance
“…This distinctive process can be used to synthesize VACNTs in bulk quantities. Labunov et al demonstrated the possibility of generating a VACNT bundle with a small diameter (10–30 nm) via the femtosecond laser irradiation of metal (Fe)-phase catalyst containing graphite [ 34 ]. Although the laser ablation process rapidly produces high-quality CNTs, its high energy consumption, limited scale-up potential, and lower grade of CNT purity limit its use in practical applications.…”
Section: Synthesis Of Vacntsmentioning
confidence: 99%
“…This distinctive process can be used to synthesize VACNTs in bulk quantities. Labunov et al demonstrated the possibility of generating a VACNT bundle with a small diameter (10–30 nm) via the femtosecond laser irradiation of metal (Fe)-phase catalyst containing graphite [ 34 ]. Although the laser ablation process rapidly produces high-quality CNTs, its high energy consumption, limited scale-up potential, and lower grade of CNT purity limit its use in practical applications.…”
Section: Synthesis Of Vacntsmentioning
confidence: 99%
“…2, c и d). Формирование графитовой оболочки, возможно, связано с частичной абляцией слоев нанотрубок и диф-фузией углерода через поверхность частиц железа [26]. Исследование методом РФЭС показало снижение доли окисленного железа при облучении импульсным ионным пучком с плотностью энергии 0.5 J/cm 2 (рис.…”
Section: обсуждение результатовunclassified
“…Another technique is the post-growth treatment based on the ablation of an array by a focused laser beam. Applications of femtosecond [17][18][19][20][21] and nanosecond [17,[22][23][24][25][26][27] pulsed and continuous [17,[28][29][30][31] lasers were considered. Due to the high longitudinal thermal conductivity of nanotubes and significantly suppressed radial heat transfer [32,33], the patterning of arrays with shortpulse lasers does not provide a decisive benefit in the quality of cut edges [17] as it is used for the ablation of dense targets [34].…”
Section: Introductionmentioning
confidence: 99%